Uma abordagem teórico-experimental do método pico-soma e suas aplicações - Araújo, Miriam Tainá Ferreira de (2018)
The sum-peak method has its use for the absolute standardization of radioisotopes emitting electromagnetic radiation under a coincidence regime. From the time of the conception of the method made in 1963 by Brinkman et al., the evolution of the experimental apparatus allowed improvements in the accuracy of the measurement of relevance parameters that are used to obtain the activity greatness for example. Some theoretical and conceptual inconsistencies were observed in the original proposal of the method, which will be carefully discussed and re-presented in this work. Therefore, the core of this research will consist of the presentation of a theoretical and experimental approach to the sum-peak method in order that the considerations attributed to it reaffirm it for application in absolute standardizations, and with that the same becomes more accepted by part of the metrological scientific community. As a consequence of these corrections, a detailed study of the uncertainties associated to the method, critical analysis of the instrumentation used and the presentation of measurements of parameters obtained for several radionuclides was done aiming at the completeness of the study presented in this manuscript.